Analysis of Profit Quality and ESG: Investor Determinants in Decision Making - Wardani, Isma; Leniwati, Driana (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2024)
This research aims to interpret the concepts of ESG and earnings quality in terms of their influence on investor decisions. Using an interpretive paradigm, this researcher tries to interpret the meaning of ESG factors and earnings quality by researching social phenomena. Data was obtained using in-depth interviews with lecturers, students and general investors who were key informants. The method used is the snowbolling system. The interview results are grouped and data reduction is carried out before being analyzed and conclusions drawn or verified. Triangulation was also carried out using different question techniques asked to ensure the validity of the data to key informants. By using triangulation techniques, researchers ensure that the data obtained is valid. The results of this research found that ESG factors and earnings quality are interpreted in material terms, environmental and social responsibility and goodness or spirituality in the context of determining factors in investment decisions. Empirically, in a broader sense, ESG factors and earnings quality are not only interpreted as financial benefits but as a reflection of investor awareness of their positive impact on the environment and social and mutual benefits.